From Placements to Partnerships: The State of Clinical Practice and Preparation. Issue 1 (1st January 2021) - Wasielewski, Laura M.; Birch, Megan L.; Bigaj, Stephen; Connelly, Vincent
ABSTRACT: The purpose of this study is to examine the scope and sequence of clinical experiences in educator-preparation programs in New Hampshire within the context of a conceptual framework for clinical practice and partnership. A statewide survey was conducted to examine existing clinical practices and to improve understanding of the nature and strength of partnerships between educator preparation programs (EPPs) and P–12 schools. Participants included EPP faculty from eight institutions of higher education (IHE). Results from this study indicate that EPPs are shifting from a placement approach for clinical experiences to a partnership approach. We also identify the scope and sequence of clinical experiences within EPPs and offer initial insights into the current state of EPP and P–12 school partnerships including strengths, challenges, and opportunities.